Listeriolysin O and Pneumolysin: Effects on intracellular calcium homeostasis and epithelial barrier integrity - Leustik, Martin; Justus Liebig University Giessen (My University, 2013)
Listeriolysin O (LLO) and pneumolysin (PLY) are two bacterial protein toxins from the family of cholesterol dependent cytolysins (CDC) that are produced by Listeria monocytogenes and Streptococcus pneumoniae, respectively. The toxins are found in all clinically relevant bacterial isolates, highlighting their importance for the virulence of these bacterial pathogens. Both LLO and PLY generate pores in the plasma membrane of host cells. High toxin concentrations directly lyse affected cells, while lower (sublytic) concentrations trigger an influx of extracellular calcium ions (Ca2+) into the cytoplasm. Ca2+ is an important intracellular second messenger. An increase in its cytoplasmic concentration ([Ca2+]i) results in the activation of signalling pathways. Both toxins were tested for their ability to create an imbalance in the Ca2+- homeostasis of epithelial cells at sublytic concentrations. It was shown that the toxins triggered a concentration-dependent increase in [Ca2+]i and caused the cells to shrink. This loss in cell surface area was dependent on the influx of extracellular Ca2+ , as it could be inhibited with LaCl3, an unspecific ion channel blocker. LLO variants harbouring single amino acid exchanges were compared to wild-type toxin to asses their functionality and gain further insights in the mechanism of pore formation. In infection experiments, it was determined that L. monocytogenes ability to invade closed epithelial monolayers was reduced by LaCl3 in a concentration-dependent manner. This implies that the LLO-induced increase in [Ca2+]i and the accompanying loss of intercellular connections are important for the bacteria to overcome epithelial barriers. Using PLY-treated epithelial cells, it was demonstrated that the toxin is able to empty intracellular Ca2+ stores independently of endogenous channels. No influx of extracellular Ca2+ was involved in this reaction, as these experiments were performed in Ca2+-free medium. Finally, the effects of PLY were compared to those of hyperosmotic conditions. It was shown that increased osmolarity and toxin administration had similar effects on the calcium homeostasis, intracellular Ca2+ stores and cell volume, which were accompanied by the translocation of the cell volume transcriptional regulator NFAT5. PLY-induced cell shrinking did not occur when PKC-alpha and MLC-phosphorylation were blocked. These inhibitors did not prevent the influx of extracellular Ca2+, suggesting that cellular signalling events are responsible for the loss in cell surface volume upon toxin treatment.

Listeriolysin O (LLO) und Pneumolysin (PLY) sind bakterielle Toxine, welche der Familie der Cholesterin-abhängigen Cytolysine (cholesterol dependent cytolysins, CDC) angehören und von Listeria monocytogenes bzw. Streptococcus pneumoniae produziert werden. Die Toxine werden von allen klinisch relevanten Stämmen dieser beiden Krankheitserreger gebildet, was ihre Bedeutung als Virulenzfaktoren aufzeigt. LLO und PLY entfalten ihre Wirkung durch die Bildung von Poren in der Zellmembran von Wirtszellen. Hohe Konzentrationen bewirken die sofortige Lyse der betroffenen Zellen, während geringere (nicht-lytische) Mengen den Einstrom von extrazellulären Calcium-Ionen (Ca2+) in das Zytoplasma ermöglichen. Unkontrollierte Veränderungen der intrazellulären Ca2+-Konzentrationen ([Ca2+]i) können verschiedenste Signalkaskaden aktivieren, da Ca2+ ein wichtiger intrazellulärer sekundärer Botenstoff ist. Es wurde untersucht ob nicht-lytische Mengen der beiden Toxine in der Lage sind, die Ca2+-Homöostase von Epithelzellen zu stören. Beide Toxine lösten einen konzentrationsabhängigen Anstieg der [Ca2+]i und eine Verminderung der Zelloberfläche aus. Beides konnte durch den Einsatz von LaCl3, einem unspezifischen Ionenkanalblocker, gestoppt werden. Dies zeigt, dass die Verminderung der Zelloberfläche durch den Einstrom extrazellulären Ca2+ ausgelöst wird. Um den Mechanismus der Porenbildung besser zu verstehen wurden LLOMutanten, bei denen einzelne Aminosäuren ausgetauscht waren, auf ihre Aktivität getestet und mit dem Wildtyp verglichen. Des Weiteren wurde durch Infektionsversuche gezeigt, dass L. monocytogenes durch LaCl3 an einer effektiven Invasion von geschlossenen Epithelzellrasen gehindert wurde. Dies spricht dafür, dass der von LLO ausgelöste Anstieg der [Ca2+]i und das damit verbundene Schrumpfen der Zellen den Bakterien hilft, die epitheliale Barriere zu überwinden. In Zellen die mit PLY behandelt wurden konnte gezeigt werden, dass das Toxin die Entleerung der intrazellulären Ca2+-Speicher unabhängig von endogenen Kanälen auslösen kann. Da die Versuche in Ca2+-freiem Medium durchgeführt wurden, basierte dieser Effekt nicht auf einem Einstrom von extrazellulärem Ca2+. Zuletzt wurde untersucht, ob sich die zellulären Reaktionen auf PLY und hyperosmolare Bedingungen unterscheiden. Die Behandlung mit Toxin und eine erhöhte Osmolarität hatten ähnliche Auswirkungen auf die Ca2+-Homöostase, die intrazellulären Ca2+- Speicher und das Zellvolumen, welche von der Translokation des Volumen6 ZUSAMMENFASSUNG 96 regulierenden Transkriptionsfaktors NFAT5 begleitet wurden. Durch die Inhibition von PKC-alpha und der Phosphorylierung von MLC konnte der von PLY ausgelöste Volumenverlust gestoppt werden. Dies verhinderte jedoch nicht den Einstrom von extrazellulärem Ca2+, was darauf hindeutet, dass das Schrumpfen der Zellen durch endogene Signalwege ausgelöst wird.
Listeriolysin O und Pneumolysin: Auswirkungen auf die intrazelluläre Calcium-Homöostase und die Epithelintegrität
Keywords: ddc:610